Algorithm of Golgi protein 73 and liver stiffness accurately diagnoses significant fibrosis in chronic HBV infection. (28th August 2017) - Cao, Zhujun; Li, Ziqiang; Wang, Hui; Liu, Yuhan; Xu, Yumin; Mo, Ruidong; Ren, Peipei; Chen, Lichang; Lu, Jie; Li, Hong; Zhuang, Yan; Liu, Yunye; et al.
Abstract: Background & Aims: Serum Golgi protein 73 (GP73) is a potential biomarker for fibrosis assessment. We aimed to develop an algorithm based on GP73 and liver stiffness (LS) for further improvement of accuracy for significant fibrosis in patients with antiviral‐naïve chronic hepatitis B virus (HBV) infection. Methods: Diagnostic accuracy evaluation of GP73 and development of GP73‐LS algorithm was performed in training cohort (n = 267) with an independent cohort (n = 133) for validation. Results: A stepwise increasing pattern of serum GP73 was observed across fibrosis stages in patients with antiviral‐naïve chronic HBV infection. Serum GP73 significantly correlated ( rho = 0.48, P < .001) with fibrosis stage and was an independent predictor for the presence of significant fibrosis ( OR, 95%CI: 1.02, 1.01‐1.03, per increase in 1 ng/mL, P < .001). Both LS (AUROC, 95%CI: 0.82, 0.77‐0.87, accuracy: 74.7%) and GP73 (AUROC, 95%CI: 0.76, 0.71‐0.82, accuracy: 71.5%) well‐predicted significant fibrosis and outperformed APRI (AUROC, 95%CI: 0.69, 0.63‐0.76, accuracy: 66%) and FIB‐4 (AUROC, 95%CI: 0.66, 0.60‐0.73, accuracy: 63.6%). Using GP73‐LS algorithm, GP73 < 63 in agreement with LS < 8.5 provided accuracy of 81.7% to excluded significant fibrosis. GP73 ≥ 63 in agreement with LS ≥ 8.5 provided accuracy of 93.3% to confirm significant fibrosis. Almost 64% or 68% of patients in the training or validation cohort could be accurately classified. Conclusions: Serum GP73 is a robust biomarker for significant fibrosis diagnosis. GP73‐LS algorithm provided better diagnostic accuracy than currently available approaches. More than 60% antiviral naïve CHB patients could use this algorithm without resorting to liver biopsy. Abstract : See Editorial on Page1605